Answer:
Let's find the recursive formula, explicit formula, and the indicated term for the given arithmetic sequences.
Sequence 1: 1, 4, 1, 10, ...
To find the recursive formula, we need to identify the pattern between consecutive terms. Looking at the sequence, we can see that each term alternates between adding 3 and subtracting 3.
Recursive formula:
a1 = 1 (the first term)
an = an-1 + (-1)^(n+1) * 3
For example, to find the 4th term (a4) using the recursive formula:
a1 = 1 (the first term)
a2 = a1 + (-1)^(2+1) * 3 = 1 + (-1) * 3 = -2
a3 = a2 + (-1)^(3+1) * 3 = -2 + 1 * 3 = 1
a4 = a3 + (-1)^(4+1) * 3 = 1 + (-1) * 3 = -2
Explicit formula:
To find the explicit formula, we need to identify the common difference. In this case, since the terms alternate between adding 3 and subtracting 3, the common difference is not constant.
Indicated term:
To find the indicated term, we need to know which term is being referred to. Please provide the term number or the position of the term in the sequence so that I can assist you further.
-----------------------------------------------------------
Sequence 2: 12, 7, 2, -3, ...
To find the recursive formula, we need to identify the pattern between consecutive terms. Looking at the sequence, we can see that each term decreases by 5.
Recursive formula:
a1 = 12 (the first term)
an = an-1 - 5
For example, to find the 4th term (a4) using the recursive formula:
a1 = 12 (the first term)
a2 = a1 - 5 = 12 - 5 = 7
a3 = a2 - 5 = 7 - 5 = 2
a4 = a3 - 5 = 2 - 5 = -3
Explicit formula:
To find the explicit formula, we need to identify the common difference. In this case, the common difference is -5.
Explicit formula:
an = 12 + (n - 1)(-5)
Indicated term:
To find the indicated term, we need to know which term is being referred to. Please provide the term number or the position of the term in the sequence so that I can assist you further.
Please provide the term number or the position of the term in the sequence so that I can help you find the indicated term.
Step-by-step explanation:
Answer:
n=26
Step-by-step explanation:
an=a+(n-1)d
80=5+(n-1)3
80=5+3n-3
80-2=3n
78/3=n
n=26
(Factorise)
X^2 + 7x + 11 = 0
(Use the quadratic formula)
Answer:
General Formulas and Concepts:
Calculus
Differentiation
Basic Power Rule:
Step-by-step explanation:
Step 1: Define
Identify
Step 2: Differentiate
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Differentiation